The Effect of Forkhead Box Class O1, Mammalian Target of Rapamycin Complex 1, Survivin, and Interleukin-17 on the Degree of Acne Vulgaris Based on Serum Levels - Hanum, Sri Yusfinah Masfah; Nasrul, Ellyza; Jusuf, Nelva Karmila; Yerizel, Eti (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Acne vulgaris (AV) is a health problem that is routinely found throughout the world and has an impact on the quality of life of sufferers. Several studies have shown that forkhead box Class O1 (FoxO1), the mammalian target of rapamycin complex 1 (mTORC1), survivin, and interleukin-17 (IL-17) play a role in the pathogenesis of multifactorial AV. AIM: The study aims to determine the relationship between serum levels of FoxO1, mTORC1, survivin, and IL-17 with the severity of AV. METHODS: This is observational research with cross-sectional design. Samples from venous blood sufferers of AV mild, moderate, and severe, each of 20 people were colected. Classification of AV was based on the criteria of Lehmann et al. Examination of serum levels of FoxO1, mTORC1, survivin, and IL-17 using the ELISA technique was done. The statistical test used was the ANOVA test and the Kruskal–Wallis test. RESULTS: The results showed that average levels of FoxO1 decreased with increasing degree of severity of AV. An average increase in mTORC1, survivin, IL-17 levels with an increase in the severity of AV was found. Statistical test results showed a significant correlation of FoxO1, mTORC1, survivin levels, and the severity of AV (p < 0.05). IL-17 levels were not related to the severity of AV (p > 0.05). CONCLUSION: This study concluded that FoxO1 levels decrease at increasing severity. Conversely, levels of mTORC1, survivin, and IL-17 increase with increasing degrees of the severity of AV.